theoretical analysis of the intermedia art form at the Solomon R. Guggenheim Museum : experimental intermedia foundation. - Solomon R. Guggenheim Museum, New York (Buenos Aires : CAYC - Centro de Arte Y Comunicacion.)
Contents : Intermedia: Process to a Transculture / by René Berger - Intermedia and Mixed Media as Sign of Crisis or a Rebirth of the Visual Arts / by Gillo Dorfles - From Leonardo to the intermedia Revolution / by Jorge Glusberg - Intermedia art / by Abraham Moles - Towards a Definition of intermedia / by Udo Kultermann
Engels
boek